Rare actinomycetes from Kuantan mangrove forest sediment - Zainal Abidin, Zaima Azira; Abdul Malek, Nurfathiah; Mohd Zin, Nur Huda; Chowdhury, Ahmed Jalal Khan (International Water, Air & Soil Conservation Society (INWASCON), 2020)
Actinomycetes are prolific secondary metabolites producer, and they are sought after for their unparalleled capability. Mangrove forests are among the underexplored locations in search of new resources of actinomycetes. Bioprospecting of actinomycetes in Kuantan mangrove forests has revealed highly diverse actinomycetes with high antimicrobial properties. Members of the rare genera successfully isolated include Micromonospora sp., Pseudonocardia sp., Verrucosispora sp., Nocardiopsis sp., Actinophytocola sp., Dietzia sp., Gordonia sp., Micrococcus sp., Mycobacterium sp., Nocardia sp., Saccharopolyspora sp. And Rhodococcus sp. These rare actinomycetes can also be added to the list of genera isolated from this ecological niche, providing solid evidence that considerable diversity of actinomycetes are distributed within Kuantan mangrove forest. PKS-I and NRPS genes are usually related to the ability to produce secondary metabolites in actinomycetes. Interestingly, several of these rare actinomycetes showed the presence of both PKS-I and NRPS genes or either gene, and this exemplifies the potential of these rare actinomycetes may possess. Further studies conducted on these rare actinomycetes may reveal their true potentials that can be exploited for natural product discovery.